Cyber Reconnaissance Techniques. - MAZURCZYK, WOJCIECH; CAVIGLIONE, LUCA (Communications of the ACM, 2021)
The article explores cyber attacks and its impact on businesses and industry as of 2021, including a deep look into reconnaissance techniques (how attackers gather information on the target). These cyber attacks include methods such as phishing, spoofing and ransomware. Counteracting reconnaissance attempts are also discussed including strengthening training, enforcing proactive approaches, and exploring cyber deception.